EFEKTIVITAS BIMBINGAN TEKNIK DALAM MENYUSUN SOAL LITERASI NUMERASI DI MI AR RAUDHAH LAWANG - Nulinnaja, Ratna; Faridah, Siti; Putra, Kivah Aha; Zulfa, Mila; Ulum, Mukhammad Bahrul; Adhim, Syahrul (Muta’allim: Jurnal Pendidikan Agama Islam, 2025)
The change in provisions in 2021 in determining student graduation will change from the national exam to a national assessment, one of its components is the AKM (minimum competency assessment). AKM consists of literacy and numeracy skills tests that are mastered by students. The AKM question is very different from the national exam. Therefore, teachers must be more disciplined in preparing themselves to equip their abilities to support the improvement of human resources in dealing with AKM which is carried out in their madrasah. To meet the needs mentioned above, technical guidance (bimtek) related to understanding numeracy is carried out. Research using Quantitative Research. In the preparation of the instrument, the variables that became the main reference for the researchers were data on the quality of teachers in preparing numeracy literacy questions before the implementation of the technical guidance and after the implementation of the technical guidance which consisted of 23 participants. The result of this research is that the implementation of technical guidance for the preparation of numeracy literacy questions is effective in improving the ability of teachers in preparing questions. Produce T-count data of 6.204650534 and t-table of 2.093024054. This means that t - count is greater than t table, so it can be concluded if H0 is rejected and H1 is accepted. So that the implementation of technical guidance is effective on the quality of numeracy literacy questions compiled by the Madrasah Ibtidaiyah teacher Ar-Raudhah Lawang. Abstrak Perubahan ketentuan pada tahun 2021 dalam menentukan kelulusan peserta didik mengalami pergeseran dari ujian nasional ke asesmen nasional, yang salah satu komponennya adalah AKM (Asesmen Kompetensi Minimum). AKM terdiri dari tes kemampuan literasi dan numerasi yang harus dikuasai oleh peserta didik. Soal-soal dalam AKM sangat berbeda dengan soal ujian nasional. Oleh karena itu, guru perlu lebih disiplin dalam mempersiapkan diri guna meningkatkan kompetensinya agar dapat mendukung penguatan sumber daya manusia dalam menghadapi pelaksanaan AKM di madrasah masing-masing. Untuk memenuhi kebutuhan tersebut, dilaksanakan bimbingan teknis (bimtek) yang berkaitan dengan pemahaman numerasi. Penelitian ini menggunakan pendekatan kuantitatif. Dalam penyusunan instrumen penelitian, variabel yang menjadi acuan utama peneliti adalah data mengenai kualitas guru dalam menyusun soal literasi numerasi sebelum dan sesudah pelaksanaan bimbingan teknis, dengan jumlah peserta sebanyak 23 orang. Hasil penelitian menunjukkan bahwa pelaksanaan bimbingan teknis dalam penyusunan soal literasi numerasi efektif dalam meningkatkan kemampuan guru dalam menyusun soal. Data menunjukkan nilai t-hitung sebesar 6,204650534 dan nilai t-tabel sebesar 2,093024054. Karena nilai t-hitung lebih besar daripada t-tabel, maka dapat disimpulkan bahwa H0 ditolak dan H1 diterima. Dengan demikian, pelaksanaan bimbingan teknis terbukti efektif terhadap peningkatan kualitas soal literasi numerasi yang disusun oleh guru Madrasah Ibtidaiyah Ar-Raudhah Lawang.